(untitled) (Bulletin of criminological association of Ukraine, 2024)
It is emphasized that the employment contract differs significantly from the category of contract in the general theoretical sense, which is connected with its following features: firstly, the employment contract provides for an agreement on the performance of professional, paid, labor activities carried out systematically at an enterprise, institution or organizations; secondly, in all cases, the parties to the employment contract are unchanged - the employee and the employer, who enter into labor relations through the conclusion of the agreement and determine the composition of mutual rights and obligations by the contract; thirdly, the employment contract is a written document, that is, it is a legal act that has an external expression and structure; it is concluded in accordance with the requirements of legal technique; fourthly, it is logical to consider an employment contract as "limitedly free", because a significant part of its content, form, mandatory conditions, features of use within the framework of individual employment relationships, terms, guarantees of conclusion are directly defined by the Labor Code and may be supplemented, but not violated ; fifthly, the direct and clear regulation has a procedure for concluding, terminating and terminating an employment contract, which takes place on the grounds specified by the Labor Code. It has been proven that an employment contract in the conditions of a simplified regime of regulation of labor relations is a special written legal act - an agreement between an employee and an employer under which the employee undertakes to perform the work specified in this agreement, and the employer undertakes to pay the employee a salary and provide working conditions necessary for performance of work